Formation of a database of auxiliary information for positioning in an environment with heterogeneous radio transparency - Mikhail N. Krizhanovsky; Olga V. Tikhonova (Российский технологический журнал)
Objectives. A pressing problem for indoor positioning systems in the absence of access to global navigation satellite systems is low positioning accuracy. This is usually associated with uneven coverage of the work area due to its geometric features or the presence of massive obstacles and walls within its boundaries. This problem is frequently resolved by placing an excessive number of positioning system base stations in the work area. This approach generates a high cost for such systems, which in turn prevents their deployment. Therefore, research and development aimed at improving the accuracy of indoor positioning systems using a minimum number of stations is of great relevance. The author previously proposed a method of increasing the accuracy of indoor positioning by taking into account obstacles known at the design stage of the system. Consideration of such obstacles in calculating the location is achieved through the mechanism of preliminary splitting of radio beacons into groups, and the allocation of reference stations of these groups among the base stations. The aim of the work is to improve this algorithm by automating the stage of preparing information about the grouping of stations.Methods. A computer simulation method was used, in order to confirm the operability of the algorithm to divide the stations of the positioning system into overlapping groups.Results. The criteria for automatic station grouping and a universal algorithm for dividing stations into groups were developed, enabling the automated preparation of the minimum necessary initial data for a program implementing an algorithm for positioning in a zone of heterogeneous radio transparency.Conclusions. Modeling of the proposed algorithm has confirmed its operability. The results obtained can be used as a significant addition to the previously proposed algorithm for taking into account obstacles when calculating distances to base stations.